2011
DOI: 10.1117/12.880600
|View full text |Cite
|
Sign up to set email alerts
|

Printable low-cost sensor systems for healthcare smart textiles

Abstract: Smart textiles-based wearable health monitoring systems (ST-HMS) have been presented as elegant solutions to the requirements of individuals across a wide range of ages. They can be used to monitor young or elderly recuperating /convalescent patients either in hospital or at home, or they can be used by young athletes to monitor important physiological parameters to better design their training or fitness program. Business and academic interests, all over the world, have fueled a great deal of work in the deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Vapor-phase microprinting of different phosphorescent OLEDs [95] and different chemically light-emitting polymers [49] can thus be seen as potential sources for arrayed detection techniques, given reports of use of printing methods to development of integrated flexible sensors. [96] Integration of wearable sensors [97] can lead to other applications such as analysis of human sweat, which contains an immense amount of diagnostic information. [98]- [102] Morris et al [103] have reported on the development of a textilebased fluid-handling platform for realtime analysis of sweat, which includes a pH sensor that depends on the use of a pH sensitive dye and a paired emitter-detector LEDs to measure color changes (Fig.…”
Section: Printed Light Sources and Imaging Systemsmentioning
confidence: 99%
“…Vapor-phase microprinting of different phosphorescent OLEDs [95] and different chemically light-emitting polymers [49] can thus be seen as potential sources for arrayed detection techniques, given reports of use of printing methods to development of integrated flexible sensors. [96] Integration of wearable sensors [97] can lead to other applications such as analysis of human sweat, which contains an immense amount of diagnostic information. [98]- [102] Morris et al [103] have reported on the development of a textilebased fluid-handling platform for realtime analysis of sweat, which includes a pH sensor that depends on the use of a pH sensitive dye and a paired emitter-detector LEDs to measure color changes (Fig.…”
Section: Printed Light Sources and Imaging Systemsmentioning
confidence: 99%